The Manifestation of English Dental Fricatives in Ghanaian Technical University Students’ Spoken English - Lawer, Richard; Asamoah, Yvette Djabaki; Hattoh-Ahiaduvor, Timothy (International Journal of Language and Literary Studies, 2025)
This study investigated the manifestation of the English dental fricatives /ð, ?/ in the speeches of Ghanaian students pursuing various HND programmes in one of the technical universities in the country. The study sought to identify the forms that the English voiced and voiceless dental fricatives manifest in the speech of the students using Distinctive Feature theory to explain the modifications. The researchers compiled sentences that contained words with the dental fricatives and made student participants read them for recording and transcription. The extracted pronunciations of the words containing the dental fricatives were compared to native speaker pronunciation using Merriam-Webster’s English Dictionary. The analysis showed that at the word's initial position, the voiceless dental fricative /?/ is articulated [t], while the voiced dental /ð/ is realised as [d]. At the word-final position, the voiceless dental fricative /?/ occurs in the speech of the participants as either [t] or [f], while the voiced dental fricative /ð/ surfaces as [d] in all contexts, including word medial position. The study recommended that teachers adopt explicit teaching of English language phonemes to make students appreciate and master the articulation of these sounds to foster accurate pronunciation.